Pneumoperitoneum with Subcutaneous Emphysema after Percutaneous Endoscopic Gastrostomy - Yalin Iscan; Bora Karip; Yetkin Ozcabi; Birol Ağca; Yesim Alahdab; Kemal Memisoglu (Case Reports in Surgery)
Percutaneous endoscopic gastrostomy is a safe way for enteral nutrition in selected patients. Generally, complications of this procedure are very rare but due to patients general health condition, delayed diagnosis and treatment of complications can be life threatening. In this study, we present a PEG-related massive pneumoperitoneum and subcutaneous emphysema in a patient with neuro-Behçet.